PROGRAM JAMINAN SOSIAl DI KABUPATEN JEMBRANA DAN KOTA YOGYAKARTA - Retnaningsih, Hartini (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2013)
This research was conducted in 2011 as a basis for discussions on the bill of Social Security Organizer Board at the House of Representatives of the Republic of Indonesia. The research background was the existence of social security program run by local governments, while the central government unable to guarantee social security for all Indonesian. Using a qualitative method, this research was conducted in Jembrana Regency of Bali Province and in Yogyakarta City, of the Special Province of Yogyakarta with a purpose to analyze the management of social security in both local governments. The result of the research shows that the social security program run by local governments is full in term of benefit for the citizens. This research recommended the importance of coordination and resources sharing between central and local governments in management area of social security.